The Comparison of Water Cooling Media Against Radiator Heat Dissipation Rate in Diesel Engines - Muhammad Sawaludin; Hasan Maksum; Wagino Wagino (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2021)
This research was motivated by the large number of consumer requests for mechanics in workshops to replace the radiator coolant in diesel engines with reguler water. This research used an experimental research approach. The experimental research was often used to find the effect of existing variable and to test the hypotheses. Based on the results of testing and data analysis that have been carried out can be seen: there was an average decrease in the temperature of the cooling media from the engine due to using the cooling media from the manufacturer, a decrease in the rate of heat dissipation between reguler water and Prestone on each rotation with an average of 4.97%, the water with TOP 1 Coolant 5.11% and the water with Toyota SLCC at 6.64%. Based on the analysis of research data and statistical tests, it was concluded that the use of cooling media from the manufacturer can increase the heat transfer coefficient of the working fluid of the radiator, so that it can reduce the engine heat level and increase the rate of coolant heat dissipation. Penelitian ini dilatarbelakangi oleh banyaknya permintaan konsumen kepada mekanik di bengkel untuk mengganti air radiator pada mesin diesel dengan air biasa Penelitian ini digolongkan pada penelitian pendekatan eksperimen. Penelitian eksperimen sering digunakan untuk mencari pengaruh di antara variabel-variabel yang ada serta untuk pengujian hipotesis. Hasil pengujian dan analisis data yang telah dilakukan dapat diketahui: Terdapat rata-rata penurunan suhu media pendingin dari mesin akibat menggunakan media pendingin asal pabrikan, penurunan laju pembuangan panas antara air biasa dengan Prestone pada masing-masing putaran dengan rata-rata 4,97%, air dengan TOP 1 Coolant 5,11% dan air dengan Toyota SLCC sebesar 6,64%. Berdasarkan analisis data penelitian dan uji statistik yang dilakukan disimpulkan bahwa penggunaan media pendingin asal pabrikan dapat memperbesar koefisien perpindahan panas fluida kerja radiator sehingga dapat menurunkan tingkat panas mesin dan meningkatkan laju pembuangan panas cairan pendingin